Mutually unbiased unitary bases - Shamsul Shaari, Jesni; N. M. Nasir, Rinie; Mancini, Stefano (American Physical Society, 2016)
We consider the notion of unitary transformations forming bases for subspaces of M(d,C) such that the square of the Hilbert-Schmidt inner product of matrices from the differing bases is a constant. Moving from the qubit case, we construct the maximal number of such bases for the four- and two-dimensional subspaces while proving the nonexistence of such a construction for the three-dimensional case. Extending this to higher dimensions, we commit to such a construct for the case of qutrits and provide evidence for the existence of such unitaries for prime dimensional quantum systems. Focusing on the qubit case, we show that the average fidelity for estimating any such transformation is equal to the case for estimating a completely unknown unitary from SU(2). This is then followed by a quick application for such unitaries in a quantum cryptographic setup.